Immunomodulatory Drugs in the Context of Autologous Hematopoietic Stem Cell Transplantation Associate With Reduced Pro-tumor T Cell Subsets in Multiple Myeloma - Di Lullo, Giulia; Marcatti, Magda; Heltai, Silvia; Tresoldi, Cristina; Paganoni, Anna Maria; Bordignon, Claudio; Ciceri, Fabio; Protti, Maria Pia (Frontiers in Immunology, 2019)
Immunomodulatory drugs (IMiDs) are effective therapeutics for multiple myeloma (MM), where in different clinical settings they exert their function both directly on MM cells and indirectly by modulating immune cell subsets, although with not completely defined mechanisms. Here we studied the role of IMiDs in the context of autologous hematopoietic stem cell transplantation on the T cell subset distribution in the bone marrow of newly diagnosed MM patients. We found that after transplantation pro-tumor Th17-Th1 and Th22 cells and their related cytokines were lower in patients treated with IMiDs during induction chemotherapy compared to untreated patients. Of note, lower levels of IL-17, IL-22 and related IL-6, TNF-, IL-1, and IL-23 in the bone marrow sera correlated with treatment with IMiDs and favorable clinical outcome. Collectively, our results suggest a novel anti-inflammatory role for IMiDs in MM.